Identification of Landslide-Prone Areas and Slip Zones Along the National Road in Bunut, Kapuas District, Sanggau Regency - Khalik, Ikdham Nurul; Nusantara, Rossie W.; Nurhayati, Nurhayati (Jambura Geoscience Review, 2026)
Landslides repeatedly disrupt the national road corridor in Bunut Sub-District, Kapuas District, Sanggau Regency (West Kalimantan), indicating that slope failure is strongly controlled by subsurface conditions that cannot be reliably inferred from surface observations alone. This study delineates landslide-prone segments and interprets the subsurface slip surface using 2D electrical resistivity imaging with the Wenner–Schlumberger array. Field measurements were conducted along three 120 m survey lines using 13 electrodes with 10 m spacing, and the data were inverted (Res2Dinv) to obtain true-resistivity sections for each line. Interpretation was guided by published resistivity classifications and the local geomorphological setting. The resistivity models reveal a clear stratification of near-surface materials, with low-resistivity zones (300 Ωm) interpreted as water-saturated, clay-rich layers and higher-resistivity zones representing comparatively drier and more permeable materials. The slip surface is consistently expressed as a sharp resistivity contrast and is interpreted at resistivity values of approximately 300–2400 Ωm at depths of about 6–18 m below ground level, suggesting a mechanically weak interface that is prone to shear under intense rainfall and pore-pressure increase. These results provide spatial constraints on slip-zone geometry that can be used to support hazard zoning and to prioritize mitigation along the road section, particularly through improved drainage, surface-water control, and slope management at locations where saturated low-resistivity materials underlie permeable surficial deposits.